Dietary Approaches for Complementary Feeding: The Greek Mediterranean Diet as a Model for Caregivers - Sofia Eleftheriou; Emilia Vassilopoulou; Anastasia Barbouni; Michael Chourdakis; Anastasia Kanellou (MDPI AG, 2024)
Background/Objectives: Complementary feeding (CF), is defined as the process of providing foods in addition to milk when breast milk or milk formula alone are no longer adequate to meet nutritional requirements. CF affects not only growth but also the subsequent development of the child's dietary preferences. The Mediterranean diet (MedDiet) is one of the most studied dietary patterns worldwide. The main purpose of this article is to provide practical guidance for CF to caregivers introducing the Greek MedDiet, summarizing the current different approaches. The evidence-based information provided could be used by developers to create a reliable digital app for CF based on Mediterranean foods and traditional dishes. Methods: An in-depth literature review of the existing guidelines and recently published research data on CF using PubMed, national recommendations, and grey literature were undertaken. Results: Practical, simple, evidence-based, comprehensive tables are presented. The tables serve as a guide to simplify the process of introducing Mediterranean foods in CF. Τhe tables consist of a total of more than 90 foods and day-to-day guidance for the first 13 weeks of CF. Furthermore, specific dietary guidance and suggestions regarding the order and content of meals during CF are given. Discussion: The tables are based on updated recommendations, summarizing the optimal feeding practices in a MedDiet-based perspective. Conclusions: Conclusively, there are significant contradictions among different organizations that present practical issues and cause confusion among caregivers. An effort was carried out to provide practical evidence-based guidance for caregivers introducing MedDiet during CF.